Anaerobic digestion of tannery sludge and tannery waste: a systematic review - Bresolin, Bianca Maria; Valentino, Francesco; Gottardo, Marco; Tuci, Giulia Adele; Alibardi, Luca (Taylor & Francis, 2025)
This review investigated the application of anaerobic digestion (AD) as a sustainable solution for managing waste generated by the leather industry and sludge from the treatment of tannery effluents. The novelty of this review is the classification and discussion of the application of AD for both sludge and solid tannery waste, either as mono- or co-digestion with other substrates. The review underscored the potential of AD as a sustainable management of tannery waste and sludge, highlighting the feasibility of AD application to address the environmental challenges of the tanning industry. The application of AD represents a promising perspective in the leather industry, due to the specific nature and the high production volumes of tannery waste and sludge. The review highlighted the impacts of tannery sludge and waste origin and characteristics on biogas yields and digestion performance. The review also indicated the limited experience on mono-digestion of tannery sludge and tannery waste, and the key challenges as process instability, the seasonal variability of feedstock and the potential inhibition due to the presence of heavy metals. Co-digestion with other substrates was identified as a promising approach to improve efficiency and yields, as well as an opportunity to stimulate the implementation of AD in the tannery sector. The experiences on AD of tannery sludge and waste remain largely at laboratory scale, and this can hinder the scale-up of applications. The review discussed the research which made substantial contributions in this area and examined the treatment opportunities for a better understanding of the topic.
Keywords: 4004 Chemical Engineering; 40 Engineering; 41 Environmental Sciences; 12 Responsible Consumption and Production; 4011 Environmental engineering; 4103 Environmental biotechnology; 4104 Environmental management; Tannery waste; tannery sludge; anaerobic digestion; renewable energy; circular economy